Effects of the Presence and Behavior of In-Group and Out-Group Strangers on Moral Hypocrisy - Bian, Junfeng; Li, Liang; Xia, Xuan; Fu, Xiaolan (Frontiers in Psychology, 2020)
Moral hypocrisy (MH) occurs when people fail to practice what they preach. Despite the prevalence of the effect of social identity on an individual’s MH, few empirical studies have explored contextual factors that may help reduce MH. By conducting two experiments based on the research paradigm of real stranger presence, we examined how in-group and out-group strangers’ presence and moral behavior may contribute to reducing MH. The results of experiment 1 demonstrated that compared with the presence of out-group strangers, the presence of in-group stranger could effectively inhibit MH (no significant difference between participants reported and actual donation proportions was obtained). The results of experiment 2 replicated and extended the results of experiment 1, first by showing that the presence of in-group strangers could effectively inhibit MH and then by revealing the influence of present strangers’ behavior (moral or hypocritical) on MH. The results indicated that strangers’ moral behavior could effectively eliminate participants’ MH, especially in the presence of in-group strangers. However, when present strangers exhibited hypocritical behavior, they exhibited no effect on participants’ MH, irrespective of the condition of in-group and out-group strangers. The current study provides empirical support for theories related to MH and moral decision making and contributes to the literature on in-group and out-group effects on MH and decision making.